Enhancing DSR protocol performance in mobile ad hoc network using ACK reply - Gani, Abdullah; Han, Q.; Anuar, N.B.; Zakaria, O. (2009)
This paper presents a new method to improve performance of DSR in Ad Hoc Network. We present an analysis of DSR protocol and propose our algorithm to improve the performance of DSR protocol by using ACK reply path as a backup route when an original route fails in Mobile Ad Hoc networks. In the traditional DSR protocol, a backup route will be initiated to transfer data in route cache when a route is broken. However, if the backup route is also failed, it will affect the overall network performance. We modify the DSR so-called Modified DSR protocol (MDSR) with the aim that the source node can still receive the ACK reply from destination node when an original route is broken, which means data packets can be transferred along with the ACK path. MDSR deploys the idea of TCP-BuS to solve unnecessary resending of lost data packets. We simulate our proposed model in NS2, compare the MDSR with DSR in the performance of end-to-end delay and packet delivery ratio. The result shows that the performance of MDSR is better than the traditional DSR protocol.